A narrative study of students' and staff's experiences of living with HIV and AIDS at Rhodes University - Tsope, Lindiwe (Rhodes University, Faculty of Humanities, Department of Sociology)
A narrative study of students' and staff's experiences of living with HIV and AIDS at Rhodes University Research on HIV and AIDS in university settings, especially research exploring the experience of living with the disease, has been minimal. As a response to the knowledge and research gaps, this thesis is a qualitative study involving students and staff living with HIV (LWH) and accessing treatment (ART) at the Rhodes University Health Care Centre. This study explored the personal and social symbolisms as well as meanings attached to living with HIV, through in-depth interviews with ten students and staff living with HIV, all purposively sampled and recruited through the Rhodes University Health Care Centre. Using social constructionism, symbolic interactionism and the theory of biographical disruption, the narratives revealed a positive and inspirational side of living with HIV and AIDS "“ especially emphasizing that PLWHA do not have to surrender to the deadly narrative of the disease. It became evident that stigma, both internal and external, largely influences illness narratives. Furthermore, the study revealed the social reconstruction of life narratives both in order to understand the illness in terms of past social experiences and to reaffirm the impression that life has a course and the self has a purpose. All participants found that accessing treatment from the Rhodes University Health Care Centre positively influenced their experiences of adherence and reconstruction of narratives. The study indicates that HIV-related interventions in place at the university need to pay more attention to the psychosocial needs of PLWH, involvement of PWLH, as well as keeping up with the continuously changing global HIV narrative. The study argues for more attention to in-depth experiences and personal narratives in HIV and AIDS, and PLWHA education at Rhodes University.
Keywords: AIDS (Disease) -- South Africa -- Makhanda; HIV infections -- South Africa -- Makhanda; College students Health and hygiene -- South Africa -- Makhanda; Universities and colleges -- South Africa -- Makhanda Employees Health and hygiene; Stigma (Social psychology); AIDS (Disease) Social aspects -- South Africa -- Makhanda; HIV infections Social aspects -- South Africa -- Makhanda; AIDS (Disease) Psychological aspects; HIV infections Psychological aspects; Health counseling -- South Africa -- Makhanda; Discourse analysis, Narrative